Reductive dehalogenase of Dehalococcoides mccartyi strain CBDB1 reduces cobalt- containing metal complexes enabling anodic respiration - Eberwein, Marie; Hellmold, Nadine; Frank, Ronny; Deobald, Darja; Adrian, Lorenz (Frontiers in Microbiology, 2024)
Microorganisms capable of direct or mediated extracellular electron transfer (EET) have garnered significant attention for their various biotechnological applications, such as bioremediation, metal recovery, wastewater treatment, energy generation in microbial fuel cells, and microbial or enzymatic electrosynthesis. One microorganism of particular interest is the organohalide-respiring bacterium Dehalococcoides mccartyi strain CBDB1, known for its ability to reductively dehalogenate toxic and persistent halogenated organic compounds through organohalide respiration (OHR), using halogenated organics as terminal electron acceptors. A membrane-bound OHR protein complex couples electron transfer to proton translocation across the membrane, generating a proton motive force, which enables metabolism and proliferation. In this study we show that the halogenated compounds can be replaced with redox mediators that can putatively shuttle electrons between the OHR complex and the anode, coupling D. mccartyi cells to an electrode via mediated EET. We identified cobalt-containing metal complexes, referred to as cobalt chelates, as promising mediators using a photometric high throughput methyl viologen-based enzyme activity assay. Through various biochemical approaches, we show that cobalt chelates are specifically reduced by CBDB1 cells, putatively by the reductive dehalogenase subunit (RdhA) of the OHR complex. Using cyclic voltammetry, we also demonstrate that cobalt chelates exchange electrons with a gold electrode, making them promising candidates for bioelectrochemical cultivation. Furthermore, using the AlphaFold 2-calculated RdhA structure and molecular docking, we found that one of the identified cobalt chelates exhibits favorable binding to RdhA, with a binding energy of approximately -28 kJ mol-1. Taken together, our results indicate that bioelectrochemical cultivation of D. mccartyi with cobalt chelates as anode mediators, instead of toxic halogenated compounds, is feasible, which opens new perspectives for bioremediation and other biotechnological applications of strain CBDB1.